Strategy of micro-environmental adaptation to cold seep among different brittle stars’ colonization - Chen, Zelin; Ma, Shaobo; Qin, Geng; Qu, Meng; Zhang, Bo; Lin, Qiang (Frontiers in Ecology and Evolution, 2022)
Diffusing fluid from methane seepage in cold seep field creates zones with physicochemical gradients and divergent ecosystems like the mussel beds and clam beds. Three species of brittle stars (Ophiuroidea) were discovered in the Haima cold seep fields, of which Ophiophthalmus serratus and Histampica haimaensis were found on top of or within mussel beds and clam beds, whereas Amphiura sp. was only collected from muds in the clam bed assemblage. Here, we evaluated the genetic signatures of micro-environmental adaptation of brittle stars to cold seep through the comparison of mitogenomes. This study provided two complete mitogenome sequences of O. serratus and Amphiura sp. and compared with those of H. haimaensis and other non-seep species. We found that the split events of the seep and non-seep species were as ancient as the Cretaceous period (~98-148 Mya). O. serratus and H. haimaensis display rapid residue mutation and mitogenome rearrangements compared to their shallow or deep-sea relatives, in contrast, Amphiura sp. only show medium, regardless of nucleotide mutation rate or mitogenome rearrangement, which may correlate with their adaptation to one or two micro-ecosystems. Furthermore, we identified 10 positively selected residues in ND4 in the Amphiura sp. lineage, suggesting important roles of the dehydrogenase complex in Amphiura sp. adaptive to the cold seep environment. Our results shed light on the different evolutionary strategies during colonization in different micro-environments.